Questionnaire Design : How to Ask The Right Questions of the Right People at the Right Time to Get the Information You Need - Moroney, William F., author.; Cameron, Joyce Anne, 1941- author. (Washington, DC : Human Factors and Ergonomics Society)
Includes bibliographical and references